The Digital Service Innovation of Access by KAI Aplication on Customer Perceived Value - Sarwono, Karenina Tryagustian; Rufaidah, Popy (Universitas Negeri Malang, 2024)
This study examines the effect of digital service innovation on customer perceived value (CPV) of the Access by KAI application. The population in this study were consumers of the Access by KAI application. This study uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 3 to analyze data and bootstrapping techniques to test hypotheses. Data were collected based on judgmental sampling through an online survey of 266 consumers who have transacted in the Access by KAI application. The results showed that digital service innovation significantly positively affects customer perceived value. These findings provide important insights for similar applications to continue optimizing their digital features to create better-added value for users. The study also provides valuable lessons learnt to enhance digital learning based on CPV.